Chamaepinnularia salina (Bacillariophyta), a new diatom species from French mineral springs (Massif Central) - Beauger, Aude; Wetzel, Carlos E.; Allain, Elisabeth; Bertin, Clotilde; Voldoire, Olivier; Breton, Vincent; Baker, Lory-Anne; Kolovi, Sofia; Biron, David; Ector, Luc (Phytotaxa, 2022)
During a survey done on the mineral springs in the French Massif Central region, a new Chamaepinnularia species (Bacillariophyceae) was found and is hereby described: Chamaepinnularia salina Beauger, C.E.Wetzel, Allain & Ector sp. nov. This new small species, with valves linear with almost parallel margins, is formally described using light and scanning electron microscopy. The central area is rectangular, forming a rather broad fascia and the raphe is straight, filiform located on an elevated sternum. Virgae between striae are developed. The ecological preferences of Chamaepinnularia salina are presented. This species is mainly in mineral springs with Na-K-HCO3 water type.